Developing Action Research Culture among Schools in Tiaong District 1 - Andal, Krystel (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The study aimed to develop an action research culture among schools in Tiaong District 1. Specifically, the study dealt with the number of research training attended, level of research training attended, number of researches conducted, and number of researches published; challenges encountered by the teachers in doing action research in terms of knowledge, schedule of workload, research resources, training related to action research; and the measures applied to address challenges in conducting action research. It employed a descriptive research method. The participants were 182 Junior High School teachers of Tiaong District 1 selected through complete enumeration. The self-made questionnaire was the main instrument used to gather data. The findings of the study revealed that most of the Junior High School teachers in Tiaong District 1 have only attended school level trainings and very few have attended national and international trainings. Moreover, most of the teachers do not have sufficient knowledge and skills in doing action research; and the major challenge that the teachers faced in doing action research was the schedule of workload that they preferred to spend their time teaching instead of doing action research. As the result implied the appropriate management of workload will aid the challenges in conducting action research as the Action Research Plan will serve as the basis for developing an action research culture among schools in Tiaong District 1.